RANCANG BANGUN WEBSITE PENJUALAN ONLINE PADA TOKO FANDHA FASHION DENGAN MENGGUNAKAN ANALISIS SWOT - Fasda Faradila (Fakultas Sains, Teknologi dan Kesehatan Universitas Sahid Surakarta, 2020)
The Fandha Fashion store still carries out a manual sales process such as cheeking the availability of goods or asking workers for availability of goods, recording every sales transaction on the book and the customers must direct come to the store in buying clothes before the sales website is used. The sales website at the Fandha Fashion store was built to facilitate buying and selling as well as marketing transactions with a good computerized system. The aims of this research is to design a Fandha Fashion online shop website in order to buyers are easier to choose models, colors, and sizes more quickly and efficiently. Data collection methods used interviews, literature and observation. The system analysis methods used the SWOT analysis method. This method measured the ability of competitors. The testing method used the black box method. The result of this study are a website with features for customers namely log in or register and shopping cart features. Admins access involves input data categories, stock, account and the owners can see or receive transaction data report recapitulated by the admin. Testing using the black box testing method involves questionnaire to 30 respondents of visitors and buyers. It shows that 15 respondents (50%) state agree, 8 respondents (30%) belongs to quite agree and 7 respondents (20%) consider normal. Thus, a sales website is easy to understand in term of appearance and user friendly.